Pelayanan Penggembalaan dan Implementasinya, Berdasarkan 1 Petrus 5:1-4 - Tonni Lolowang; Mujiono Mujiono; Herling Fredriek Bulahari (Pusat Riset dan Inovasi Nasional, 2025)
Pastoral ministry is a divine calling that demands faithfulness, vigilance, and wholehearted love in caring for God’s flock. However, in the reality of ministry, many church shepherds face complex and burdensome challenges in fulfilling this responsibility. A failure to understand and implement authority based on the character of Christ often becomes the root problem in pastoral ministry. This study aims to explore the dynamics of pastoral ministry in the context of today’s church, particularly in light of 1 Peter 5:1–4. The approach used is qualitative descriptive, based on a literature review, with a focus on relevant theological and pastoral works. The findings reveal that many pastors experience spiritual and emotional exhaustion, especially when their ministry lacks support from an adequate organizational structure, or when the congregation’s expectations are misaligned with the church’s mission. In this context, true shepherding—as explained by figures such as Bill Lawrence and Phil Pringle—must be rooted in Christ as the Head of the Church. A pastor is called to serve with humility, not to dominate or pursue personal interests. Furthermore, a deep understanding of the biblical metaphor concerning the relationship between shepherd and sheep is essential to avoid distortions in meaning and deviant ministry practices. An emphasis on love, responsibility, and exemplary conduct becomes the foundational framework for building an integrous pastoral ministry. This study concludes that pastoral ministry will be more effective when supported by clear church organizational policies, a deep theological foundation, and pure ministry motivations. Thus, pastoral ministry is not merely an administrative task, but a manifestation of God's love expressed through the lives of His servants.